ANALISIS KETERAMPILAN KERJA ILMIAH DALAM PRAKTIKUM KOLOID BERBASIS INKUIRI TERBIMBING PADA SISWA KELAS XI IPA 2 MAN 2 PONTIANAK - Maimuna Maimuna; Hairida Hairida; Dini Hadiarti (Jurnal Ilmiah Ar-Razi, 2016)
ABSTRACTThis study aimed at describing thescientific work skill in guided inquiry-based colloid lab on XI IPA 2 students of MAN 2 Pontianak. Using descriptive method, this study employed 29 students as the subjects. The data collection techniques used were observation and interview. While thedata collection tools used were and interview guides. The average skillin formulating the problem was 100%, the skill informulating the hypothesis was 95.40%, the skill in conducting experiments was 86.59%, the skill in observing experimental results was 83.14%, the skillin analyzing the experimental results was 73.56%, and the skillin formulatingthe hypotheses was 70.12%. It can be concluded that the students of XI IPA 2 MAN 2 Pontianak are considered excellent as their overall average of scientific work skill inguided inquiry-based colloid lab was 84.48%.Keywords: Job Skills scientific, lab colloid-based guided inquiry